'Aid intervention' in the occupied Palestinian territory: do Gulf Arab donors act differently from Western donors?. Issue 3 (4th May 2019) - Turner, Mandy
ABSTRACT: This contribution uses an expanded conceptualisation of intervention based on the understanding of it as an attempt to influence, negatively or positively, the political context/direction of a country/situation. It does this through the concept of 'aid intervention' in the conflict-context of the occupied Palestinian territory (OPT). Based on over 12 years of research experience of aid donors in this context, this contribution compares the stated principles, as well as the methods and practices, of the main Western (USA and EU) and non-Western (Gulf Arab) states involved in providing aid. It is argued that while there are some interesting differences, there are some striking similarities, thus offering a critique and corrective to the prejudices that underpin the distinctions of 'Western' and 'non-Western', 'liberal' and 'illiberal'.